Elderly Participation in Non-Communicable Disease Posbindu Services in Rembang Regency - Siti Rochmah; Cahya Tri Purnami; Farid Agushybana (Window of Health : Jurnal Kesehatan, 2023)
Non-communicable diseases have increased from 39.8% in 1990 to 69.9% in 2017, and some are suffered by the elderly. The government guarantees the availability of elderly health services through posbindu, but the participation of the elderly in posbindu services has not met the 100% target. This study aimed to analyze what factors can affect the elderly in utilizing Posbindu PTM in Rembang Regency. The type of research used is quantitative research with a cross-sectional approach. The total population is 60,726 elderly in Rembang Regency. The sampling method is random sampling, and the sample size is determined using the Lemeshow formula; a number of 400 elderly people are obtained. The instrument was used as a questionnaire with the interview method. Data were analyzed using Chi-square and multiple logistic regression. The relationship test results showed a p-value <0.05 between the variables of health worker support, family support, perceived vulnerability, perceived severity, perceived benefits, and perceived obstacles to using Posbindu PTM. The results of this study obtained a lack of utilization of Posbindu PTM by 65.5%. The most influential factor in the multivariate analysis was perceived vulnerability p value = 0.0001, OR = 9.153, 95% CI = 4.595-18.230, while family support proved to have no significant effect (p-value = 0.259). The conclusion of this study is that the perceived vulnerability variable has the most influence on the utilization of Posbindu PTM. It is suggested that there should be efforts to increase the knowledge of the elderly so that the elderly have literacy about their illness so that they can increase the participation of the elderly in posbindu services